Abundance of bacteria and histopathologic findings in the small intestinal mucosa of dogs with chronic inflammatory enteropathies - Cintia R. R. Queiroz-Machado; Mohsen Hanifeh; Enrico Bottero; Chi-Hsuan Sung; Patricia Eri Ishii; Roberto M. C. Guedes; Raphael R. Wenceslau; Susanne Kilpinen; Thomas Spillmann; Jonathan A. Lidbury; Joerg M. Steiner; Jan S. Suchodolski; et al. (PLoS ONE, 2025)
Chronic inflammatory enteropathy (CIE) is often retrospectively classified as food-responsive, steroid-responsive, and antibiotic-responsive enteropathy. However, whether bacterial fluorescence in situ hybridization or histopathologic findings can predict treatment response has not been extensively investigated. The study aimed to investigate the relationship between clinical disease activity, bacterial abundance, and histopathologic scores in the small intestine of dogs with different subtypes of CIE. Samples from the duodenum and ileum from 54 dogs with different categories of CIE and 11 control dogs were used for investigation of bacterial abundance with fluorescence in situ hybridization and histopathologic changes. Duodenal bacterial abundance did not differ among the four groups. While the abundance of total superficial bacteria and attached bacteria was increased in the ileal mucosa of dogs with antibiotic-responsive enteropathy compared to control dogs, it was not significantly different between the CIE groups. Summative histopathologic scores did not differ between the different CIE categories. The histopathologic findings, including neutrophilic inflammation, were variable and most of the parameters overlapped between the different CIE. There was a positive correlation between duodenal and ileal histopathologic scores and the canine inflammatory bowel disease activity index. In summary, increased bacterial abundance and histopathologic scores were found in CIE compared to healthy dogs, but these findings could not predict the treatment response for the different categories of CIE. Fluorescence in situ hybridization for bacteria in small intestinal biopsies had limited utility in distinguishing between different CIE types.